Systematic Study of Some Epiphytic Algae (Non-diatoms) on the Submerged Parts of Water Hyacinth [Eichhornia crassipes (Mart.) Solms-Loubach] Found in Laguna de Bay, Philippines - Eldrin DLR. Arguelles (Tropical Life Sciences Research, 2019)
Taxonomic study on the composition of epiphytic algae living on submerged leaf and root tissues of macrophyte Eichhornia crassipes (Mart.) Solms-Loubach, found at Laguna de Bay, Philippines was conducted. In total, 21 algal taxa were identified: seven Cyanophyceae, six Euglenophyceae, five Chlorophyceae, two Trebouxiophyceae and one Klebsormidiophyceae. Of these taxa, the occurrence of two rare cyanobacteria, Pseudanabaena minima (G.S. An) Anagnostidis and Synechococcus nidulans (Pringsheim) Komárek are reported for the first time in the Philippines. Two species are also reported here for the first time in the Philippines based on current taxonomic nomenclature and these are Pseudopediastrum boryanum (Turpin) E. Hegewald, Phormidium granulatum (Gardner) Anagnostidis which were based on the former names of Pediastrum boryanum (Turpin) Meneghini and Oscillatoria granulata Gardner, respectively. These taxonomic records are considered important basal information in enriching the knowledge about the diversity and habitat distribution of cyanobacteria and microalgae on macrophytes found in freshwater habitats in the Philippines.